A CONSPIRACY TO MURDER SENNACHERIB? A REVISION OF SAA 18 100 IN THE LIGHT OF A RECENT JOIN. (December 2021) - Dalley, Stephanie M.; Siddall, Luis R.
Abstract : SAA 18 100 (ABL 1091) is a cuneiform text that has been at the heart of historical reconstructions of the assassination of the Assyrian king, Sennacherib, since it was first properly studied by S. Parpola in 1979. In 2005, J. C. Fincke discovered a new fragment of the document (28-3-23 [K.21923]) and joined it to the then known fragment (80-7-19, 28). Fincke's join offers the opportunity to study the tablet anew. We present the first full scholarly edition of the fragments and a new historical interpretation of the text that challenges the accepted understanding of its date, nature, content, and the information it provides on the assassination of Sennacherib. SAA 18 100 appears to be an archival copy of a letter originally sent to Nineveh that reported on matters concerning the Assyrian court heard in Babylonia. The best-preserved report concerns a supposed plot looking to frame the king's son, Urdu-Mullissu, in a conspiracy, and might be a product of the pro-Esarhaddon machinations of the royal court during the final years of Sennacherib's reign.